2022
DOI: 10.1021/jacs.2c06333
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Covalent Organic Framework Enabling Photostimulus-Responsive Devices

Abstract: Two-dimensional covalent organic frameworks (2D COFs) feature graphene-type 2D layered sheets but with a tunable structure, electroactivity, and high porosity. If these traits are well-combined, then 2D COFs can be applied in electronics to realize functions with a high degree of complexity. Here, a highly crystalline electroactive COF, BDFamide-Tp, was designed and synthesized. It shows regularly distributed pores with a width of 1.35 nm. Smooth and successive films of such a COF were fabricated and found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…A clearer observation revealed several weak diffraction peaks at 2θ = 6.26, 7.14, 9.30, and 12.04°, which may be ascribed to the corresponding (110), (200), (210), and (220) planes (Figure S3). There was a broad peak at about 24.78°, indicating an interlayer π–π stacking distance of <3.5 Å, typical of a reasonable value for π–π stacking systems . Both COF-TAPT-BPDA and COF-TAPP-BPDA prepared under the same conditions revealed higher crystallinity with similar hexagonal crystalline structures.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A clearer observation revealed several weak diffraction peaks at 2θ = 6.26, 7.14, 9.30, and 12.04°, which may be ascribed to the corresponding (110), (200), (210), and (220) planes (Figure S3). There was a broad peak at about 24.78°, indicating an interlayer π–π stacking distance of <3.5 Å, typical of a reasonable value for π–π stacking systems . Both COF-TAPT-BPDA and COF-TAPP-BPDA prepared under the same conditions revealed higher crystallinity with similar hexagonal crystalline structures.…”
Section: Resultsmentioning
confidence: 89%
“…There was a broad peak at about 24.78°, indicating an interlayer π−π stacking distance of <3.5 Å, typical of a reasonable value for π−π stacking systems. 18 Both COF-TAPT-BPDA and COF-TAPP-BPDA prepared under the same conditions revealed higher crystallinity with similar hexagonal crystalline structures. (Figure S9).…”
Section: Resultsmentioning
confidence: 92%
“…Such organic framework material can either extend into two or three dimensions 7 . Extensive exploration of new structures 8 10 , topologies 11 – 13 , methods of fabrication 14 18 , and applications 19 23 of COFs is motivated by a heightened control of atom and pore distributions as well as the properties that derive therefrom. One successful approach to COF crystal synthesis relies on dynamic covalent chemistry 24 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, photoresponsive materials have attracted extensive attention because light is a kind of green and environmentally friendly clean energy that can be regulated remotely, rapidly, and accurately. 13−17 Compared to the photoresponsive inorganic transition-metal oxide, photoresponsive organic molecules with reversible conformational changes, such as spiropyran, 18,19 diarylethenes, 20,21 and azobenzene, 22−26 have been widely used in controllable liquid transport, 11 information storage, 27 sensors, 28 anticounterfeiting, 29,30 etc. In particular, the azobenzene and its derivatives demonstrate the obvious variation of the spatial structure and the dipole moments between the stable trans state and the metastable cis state, which endows the azobenzene-containing materials with fascinating properties of a reversible structural change or surface properties upon photoirradiation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Today, various materials can respond to external stimuli such as pH, , temperature, humidity, , and magnetic field, , which have been widely used in the fabrication of smart functional devices. Among them, photoresponsive materials have attracted extensive attention because light is a kind of green and environmentally friendly clean energy that can be regulated remotely, rapidly, and accurately. Compared to the photoresponsive inorganic transition-metal oxide, photoresponsive organic molecules with reversible conformational changes, such as spiropyran, , diarylethenes, , and azobenzene, have been widely used in controllable liquid transport, information storage, sensors, anticounterfeiting, , etc. In particular, the azobenzene and its derivatives demonstrate the obvious variation of the spatial structure and the dipole moments between the stable trans state and the metastable cis state, which endows the azobenzene-containing materials with fascinating properties of a reversible structural change or surface properties upon photoirradiation. To date, numerous outstanding studies have been conducted on novel photoresponsive polymers bearing azobenzene groups as side chains for applications in the fabrication of functional devices and smart surfaces. , For example, Tian et al reported a simple strategy for the fabrication of novel photoresponsive semiconductor devices via incorporation of two types of azobenzene groups in the side chain of the conjugated D–A polymer .…”
Section: Introductionmentioning
confidence: 99%